التعبيرات غير اللفظية في رواية مالك الحزين: مقاربة سيميائية عرفانية - الشهاوي، محمود ربيع إسماعيل Alshahawi, Mahmoud Rabia Ismail (Natural Sciences Publishing, 2021)
In This study, I selected the novel "The Heron" by (Ibrahim Aslan). To be a valid sample through which I can obtain results that demonstrate the validity of the experiment, and the choice of "heron" came because most of the studies I dealt with were reduced to the place element, apart from the other elements that (Aslan) relied on during the creation of the heron It represents his vital experience and his mental Perception Through it، The non-verbal expressions in the novel "The Heron" are one of the most prominent reasons that I relied on, and based on what was mentioned, it was based - in this study - on the semiotic method; Because it is based on the sign in reaching the meaning on the one hand, and on the cognitive approach to determining the nature of the secular metaphors present in non-verbal expressions in order to reveal their semantic intent on the other hand.
لقد عمدت في هذه الدراسة إلى اختيار رواية "مالك الحزين" لـــــ (براهيم أصلان)؛ لتكون عينة صالحة أستطيع من خلالها الحصول على نتائج توضّح صدق التجربة، وجاء اختيار "مالك الحزين" بسبب اختزال أغلب الدراسات التي تناولتها على عنصر المكان، بمنأى عن العناصر الأخرى التي استند إليها (أصلان (أثناء خلق "مالك الحزين" وتمثل تجربته الحيوية وتصوره الذهني من خلالها، وتأتي التعبيرات غير اللفظية في رواية "مالك الحزين" أحد أبرز الأسباب التي اتكأت عليها، وبناء على ما ذكر فقد استندت في هذه الدراسة إلى المنهج السيميائي؛ لارتكازه على العلامة في الوصول إلى المعنى من جهة، وإلى المنهج العرفاني لتحديد ماهية الاستعارات العرفانية (الاتجاهية، الأنطولوجية، البنيوية) الموجودة في التعبيرات غير اللفظية؛ بُغية الكشف عن قصديتها الدلالية من جهة ثانية.
Keywords: اللغة العربية -- النحو -- النحاة -- البلاغة اللغوية -- الدراسات البلاغية